Pengaruh Persepsi Pengusaha Kecil Dan Menengah Mengenai Penggunaan Sistem Informasi Akuntansi (Studi Kasus pada Kota Metro) - Goenawan Goenawan; Leni Marlina; Chairul Anwar (Universitas Bandar Lampung (UBL), 2012)
Financial accounting information flow from smaller companies is very helpful to know how the development of the capital structure of the company, how, how much profit the company earned in a given period. Many small and medium enterprises have difficulties in understanding accounting information. The difficulties experienced by small entrepreneurs are generally not able to practice accounting information adequately. Seeing so much of the role and usefulness of accounting information in creating the current financial information to support the survival of (going concern), then through the secondary industry this study wanted to find out the extent of the influence of peneyelengaraan and the use of accounting information to small entrepreneurs perceptions on the accounting information.